Field-simulated droughts affect elemental leaf stoichiometry in Mediterranean forests and shrublands - Sardans, Jordi; Rivas-Ubach, Albert; Estiarte, Marc; Ogaya, Romà; Penuelas, Josep (ACTA OECOLOGICA-INTERNATIONAL JOURNAL OF ECOLOGY, 2013)
This study evaluated the change induced by the year season and by experimentally induced drought on foliar element stoichiometry of the predominant woody species (Quercus ilex and Erica multiflora) in two Mediterranean ecosystems, a forest and a shrubland. This study is based in two long-term (11 yr) field experiments that simulated drought throughout the annual cycle. The effects of experimental droughts were significant but weaker than the changes produced by ontogeny and seasonality. Leaf N and P concentrations were higher in spring (the main growing season) in E. multiflora and, in Q. ilex in autumn (a period of additional growth). Leaf N:P ratios were lower in spring. In Q. ilex, the highest leaf K concentrations and leaf K:P ratios, and the lowest leaf C:K and N:K ratios, occurred in summer, the season when water stress was greatest. In E. multiflora, leaf K concentrations and K:P ratios were highest, and leaf C:K and N:K ratios were lowest in the plants from the drought-treated plots. The plant capacity to change K concentrations in response to seasonality and to drought is at least as great as the capacity to change N and P concentrations. The results underscore the importance of K and its stoichiometry relative to C, N and P in dry environments. These results indicate first, that N:P ratio shifts are not uniquely related to growth rate in Mediterranean plants but also to drought, and second, that there is a need to take into account K in ecological stoichiometry studies of terrestrial plants. (C) 2013 Elsevier Masson SAS. All rights reserved.
Keywords: climate change; Drought; Growth rate hypothesis; N:P; nitrogen; Ontogeny; phosphorus; Potassium